Focal nerve enlargement is not the cause for increased distal motor latency in ALS: Sonographic evaluation. Issue 8 (August 2015) - Mori, Atsuko; Nodera, Hiroyuki; Takamatsu, Naoko; Shimatani, Yoshimitsu; Maruyama, Keiko; Oda, Masaya; Izumi, Yuishin; Kaji, Ryuji
Highlights Focal conduction slowing at the median nerve at the wrist in ALS has been frequently reported, but its etiology has been elusive. Sonography of the median nerve showed lack of swelling of the median nerve at the wrist in ALS despite of focal conduction slowing. The mechanism of selective focal conduction dysfunction in ALS is unlikely to be compressive or demyelinative, rather might be related to preferential involvement of the distal portion of the median nerve.